DETERMINANTS OF LIQUIDITY AND THEIR EFFECT ON FINANCIAL PERFORMANCE OF CONSTRUCTION SERVICES SOE COMPANIES - Salim, M. Noor; Maududy Ary , Muhammad (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to analyze the effect of working capital turnover, cash turnover and account receivable turnover on financial performance through mediation of company liquidity. This study takes the subject of four construction service companies in Indonesia in the period before and after the restructuring and revitalization (2011-2018). Determination of the sample is done by saturation sampling technique. Data analysis with panel data regression test through Eviews program. The results of partial data analysis show that: (1) working capital turnover has a significant effect on company liquidity, however cash turnover and account receivable turnover do not have a significant effect on company liquidity; (2) working capital turnover has a significant effect on the company’s financial performance, but cash turnover and account receivable turnover do not have a significant effect on the company’s financial performance; and (3) liquidity has no significant effect on the company’s financial performance.